Urban sustainability in pedestrian street in downtown areas : Case study of bauru - Brazil - Magagnin, Renata Cardoso [UNESP] (2012)
The pedestrian streets in central areas of cities are mainly characterized by the concentration of commerce and financial and service sectors. The uses and users of those spaces are influenced by spatial quality of their urban design. Among the positive aspects that influence the spatial quality are: urban accessibility, microclimates, state of maintenance of public space and buildings and the valuation of historical heritage. In this context, this research focuses on a pedestrian street located in the central area of the city of Bauru-SP, Brazil. This paper analyzes the level of sustainability of that pedestrian street through the following aspects: microclimate, accessibility and preservation of architectural heritage. This research used different methodologies (questionnaires, microclimatic monitoring, photographic survey of urban space and facades, survey of heritage buildings among others) to analyze the conditions of urban accessibility, thermal comfort of the users, state maintenance of urban space and the preservation and enhancement of heritage facades in order to measure the level of sustainability of that pedestrian street. This paper contributes to studies on the quality of streets in downtown areas, sustainability, public policy and urban planning; and it also contributes to the formulation of municipal policies aimed at providing a better quality of life for users.